Heavy metal fixation of lead-contaminated soil using Morchella mycelium. (15th November 2021) - Wang, Yazhou; Tan, Renhao; Zhou, Li; Lian, Jie; Wu, Xudong; He, Rong; Yang, Fan; He, Xinsheng; Zhu, Wenkun
Abstract: With the exploitation of lead-zinc deposits, lead content around mining areas has seriously exceeded the recommended level. The most challenging problem is how to reduce lead contamination in soil efficiently. In this study, we developed a method to remediate lead-contaminated soil by adding Morchella mycelium. First, we compared the repair effects of mycelium and hyperaccumulator by conducting pot experiments. Then, we investigated the mechanism through which mycelium repairs lead-contaminated soil by conducting simulation experiments. Results showed that using mycelium was a more efficient way to repair soil than using hyperaccumulator. Compared with the untreated group, mycelium reduced the lead content of crops by 34.83 % and raised dry biomass by 134.05 % when lead addition was 800 mg/kg. After mycelium fixation, soil catalase, urease, cellulase, and sucrase activities were significantly enhanced, and the bioavailability of lead decreased significantly. The lead solution exposure simulation test showed that Morchella mycelium immobilized lead due to its extracellular secretions. That is, mycelium secreted metabolites and lead to form salt crystals, reducing bioavailable lead content. In addition, Morchella mycelium restoration may effectively improve soil fertility and increase crop yields. Thus, mycelium may be used successfully in alternative green repair methods for environmental heavy metal remediation. Graphical abstract: Image 1 Highlights: Morchella has an important advantage, it can grow directly on unsterilized soil. Morchella mycelium restoration effectively improve increase crop yields. The bioavaila-bility of lead decreased significantly after mycelium fixation. Mycelium secreted metabolites and lead to form salt crystalst.